Audit Committee Characteristics and Financial Restatements: Evidence from Two-Tiered System - Melyana Handoko; Tarsisius Renald Suganda; Rino Tam Cahyadi (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2025)
This study aims to examine the relationship between audit committee characteristics and the occurrence of financial restatements in Indonesia’s Consumer Business, Energy, and Manufacturing sectors, with a focus on the unique context of Indonesia as the research setting. Financial restatements, often referred to as an